The Drug Management Information System in Mulia Pharmacy Web-Based - Fira Mayori; Nurmaliana Pohan (Jurnal Sains dan Teknologi Informatika, 2023)
The web-based drug management information system at Mulia Pharmacy is a system used to manage drug data and process drug transactions online. However, currently the existing system still uses the manual method and has several problems, such as limitations in updating drug data in real-time; so it takes a long time to get drug information in an emergency, long report generation. Therefore, an information system is needed that includes drug data management starting from purchasing drugs to suppliers, drug sales to the general public as well as in preparing drug stock reports. The purpose of this research is to improve the old system by creating a computerized information system for managing drug data. The benefits of this system facilitate the process of recording drug data, be it buying or selling. The research methodology used in the development of a new system may include preliminary studies, system design, system implementation, and system evaluation and maintenance. In this study, a qualitative approach was used with the case study research method to obtain in-depth information about the web-based drug management system at Mulia Pharmacy and how the newly designed system can overcome existing problems. With the development of a drug management information system at Mulia Pharmacy that is web-based which is better and has been integrated, it is hoped that it will facilitate the management of drug data and the online drug transaction process, and can overcome other problems..